Working with the Grain : How Amenable to Digital Transformation Are the Monitoring and Repair of Rural Water Points in Tanzania? - Kissling, W.D. (2020)
Rural water services are still not working for poor people. The rising mobile phone penetration in Africa raised hopes in the development community that mobile phone–based ICT platforms could digitally transform rural water supply services. Our approach to platform development is “working with the grain” of the information ºow between citizens and district ofªcials, in view of emerging funding opportunities for water point repair in Tanzania (Payment-byResults). We distinguish between discretionary tasks and transaction-intensive tasks in the information ºow. An ICT platform for monitoring and repairing rural water points should start by digitally transforming tasks with high transaction intensiveness and low discretion that occur outside village and district institutions. Actors in rural water supply should collaboratively simplify formal rules and procedures that govern information ºows within local institutions before considering further digitization